Risk work in NHS 111: the everyday work of managing risk in telephone assessment using a computer decision support system. (19th May 2017) - Turnbull, Joanne; Prichard, Jane; Pope, Catherine; Brook, Simon; Rowsell, Alison
Abstract : The substitution of clinical with non-clinical staff to triage and manage calls in the NHS urgent care services is one of the number of measures designed to meet growing health services demand. The deployment of a Computer Decision Support System 'NHS Pathways' to support this work has created a new type of health worker and a new form of risk work. In this article, we examine how call handlers manage, experience and respond to risk in their everyday practice of telephone assessment. We draw on data from an ethnographic study of 5 NHS 111 sites involving 356 h of observation plus 6 focus groups with 47 health services staff in 2011–2012. We found that there was a 'risk problem' involving balancing the competing demands of assessing patients safely against rationing limited health resources. The new service used technology to support risk management but this technology also created risk work for call handlers, clinicians and patients. We found that call handlers engaged in risk work that involved interpretation, judgement and flexibility in using NHS Pathways. Call handlers also deferred some risk work to both clinicians and patients/callers. Risk work now involves 'making the technology work' and much of this work has been delegated to non-clinical call handlers. These new healthcare workers are interpreters of risk. Risk work creates a sense of responsibility (and sometimes anxiety) for these non-clinical call handlers.